If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -1(2x + 7) = 3 + 4(x + -9) Reorder the terms: 6x + -1(7 + 2x) = 3 + 4(x + -9) 6x + (7 * -1 + 2x * -1) = 3 + 4(x + -9) 6x + (-7 + -2x) = 3 + 4(x + -9) Reorder the terms: -7 + 6x + -2x = 3 + 4(x + -9) Combine like terms: 6x + -2x = 4x -7 + 4x = 3 + 4(x + -9) Reorder the terms: -7 + 4x = 3 + 4(-9 + x) -7 + 4x = 3 + (-9 * 4 + x * 4) -7 + 4x = 3 + (-36 + 4x) Combine like terms: 3 + -36 = -33 -7 + 4x = -33 + 4x Add '-4x' to each side of the equation. -7 + 4x + -4x = -33 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + 0 = -33 + 4x + -4x -7 = -33 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 = -33 + 0 -7 = -33 Solving -7 = -33 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 2x+1=3+4x | | m^2+16m=-49 | | -8m-10+6m=36 | | 5x^2+18x+45=0 | | 5x+9=15-6 | | 1+8y=-32 | | X^2-4x-12y+16=0 | | 8+6x+3x=-10 | | 3k-15=78 | | 8(5n-4)+8=-264 | | 6c-64=80 | | Y/3-15=-6 | | -7m-5=37 | | 4m+70=-30 | | 8y+4(7+y)=3(y-2)+10 | | p(t)=(348)3t/4 | | 4+7x-5x=-6 | | W=2x+2y | | 11(x)=4(y) | | X^4-y^3=17 | | x(3x)(-12x+2)=y | | X^4-y^3=17solve | | 30/3.14 | | y/33 | | 8n+15.2=1.6 | | x^2+6=216 | | 6x+27+8x+72=-92 | | 8x=4+5x | | -8m+6m=32 | | In5-In3/In2 | | 8m-27=-47+3m | | 180=((2x)+1)+((5x)-3) |